Rebuilding the species pool within a phylogenetic framework - Sijia Yuan; Yuhao Zhao; Jean-Philippe Lessard; Thomas E. Martin; Thomas J. Matthews; Xingfeng Si (Trends in Ecology & Evolution, 2026)

Safeguarding the role of humans in conservation science in the age of AI - Amanda E. Bates; Bea Maas; Vanessa M. Adams; John F. Benson; Dominick A. DellaSala; Arash Ghoddousi; Varun R. Goswami; Janice Ser Huay Lee; Javier Nori; Valeria Rinaudo; Xingfeng Si; Orsolya Valkó; et al. (Biological Conservation, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

How much is too much? Grazing intensity governs wildlife–livestock interactions in alpine meadows - Yangheshan Yang; Mark S. Boyce; Xincheng Li; Xingfeng Si (Biological Conservation, 2026)

Reconceptualizing Imperfect Detection From Statistical Noise to a Lens for Ecological Signal - Yue Wang; Yuhao Zhao; Morgan W. Tingley; Xingfeng Si (Global Change Biology, 2026)

Contrasting effects of habitat fragmentation on community stability of breeding and wintering birds in urban green spaces - Xiangxu Liu; Di Zeng; Yuhao Zhao; Shao-peng Li; Shaopeng Wang; Bicheng Li; Xiao Yuan; Shunqi Bo; Xingfeng Si (Urban Forestry & Urban Greening, 2025)

Island Biogeography and Life‐History Traits Stabilize Island Bird Communities - Yuhao Zhao; Di Zeng; Thomas J. Matthews; Dylan Craven; Morgan W. Tingley; Shaopeng Wang; Shao‐peng Li; Ping Ding; Xingfeng Si (Global Change Biology, 2025)
Islands are model systems for testing and developing ecological theories. Despite extensive research on island biodiversity, the importance of the biogeographic context for biodiversity–stability relationships is poorly understood. We addressed this knowledge gap by integrating the Equilibrium Theory of Island Biogeography (ETIB) with a functional perspective to explore island biodiversity–stability relationships. We conducted annual breeding bird surveys across 36 land‐bridge islands in eastern China over 13 years. Using this long‐term dataset, we quantified avian temporal community stability (and its components of population stability and population asynchrony) and tested how island biogeographic factors (i.e., island area, isolation, colonization rates, and extinction rates) and biodiversity facets (i.e., species richness, average population size, and life‐history traits) interact to influence stability. We found larger islands supported higher species richness due to colonization–extinction dynamics and habitat heterogeneity, which in turn promote both population stability and asynchrony. In addition, larger islands harbored larger and individually more stable populations over time. In contrast, island isolation had a weak net effect on stability, as its positive and negative influences through different pathways balanced each other out. Furthermore, species with ‘fast’ life‐history traits, characterized by shorter generation times, contributed more to community stability. These findings clarify multiple pathways through which biogeographic factors shape avian community dynamics on islands. Our study thus illustrates how island biotas maintain community stability and provides insights for preserving biodiversity and ecosystem functioning in fragmented or island‐like landscapes facing rapid biodiversity loss in an era of global change.

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Spatiotemporal dynamics of migratory birds reshape seed dispersal and conservation implications on fragmented islands - Wande Li; Ingo Grass; Chen Zhu; Thomas Hiller; Marit Kinga Kasten; David Becker; Sara Tassoni; Ping Ding; Xingfeng Si (Biological Conservation, 2025)

Seasonality, worker caste, and the interaction between island area and habitat type influence the thermal tolerance of ants on fragmented habitat islands - Yuhao Zhao; Chenxiao Wu; Chi Man Leong; Jiaxin Li; Wei Lu; Yijuan Xu; Xingfeng Si; Nathan J. Sanders (Marine Life Science & Technology, 2025)

Architecture and stability of tripartite ecological networks with two interaction types - Yangyang Zhao; Zhicheng Zhang; Xiyang Hao; Yongjun Zhang; Xingfeng Si; Chuan Yan (Ecology, 2025)
Over the past few decades, studies on empirical ecological networks have primarily focused on single antagonistic or mutualistic interactions. However, many species engage in multiple interactions that support distinct ecosystem functions. The architecture of networks integrating these interactions, along with their cascading effects on community dynamics, remains underexplored in ecological research. In this study, we compiled two datasets of empirical plant–herbivore/host–parasitoid (PHP) and pollinator–plant–herbivore (PPH) networks, representing two common types of tripartite networks in terrestrial ecosystems: antagonism–antagonism and mutualism–antagonism. We identified the patterns of subnetwork structures and interconnection properties in these networks and examined their relationships with community stability. Our findings revealed distinct pathway effects of network architecture on persistence and local stability in both PHP and PPH networks, with subnetwork modularity and nestedness showing a few strong direct effects and mediating the indirect effects of subnetwork size and connectance. In PHP networks, subnetwork modularity enhanced persistence and local stability, whereas subnetwork nestedness directly undermined them. However, both subnetwork topologies consistently mediated the destabilizing effects of subnetwork size and connectance on the entire network. In PPH networks, persistence was primarily affected by the plant–herbivore subnetwork, while the size, connectance, and modularity of different subnetworks had opposing effects on local stability. Regarding interconnection properties, the correlation of interaction similarity destabilized PHP networks, whereas the correlation of interaction degree promoted local stability in PPH networks. Further analysis indicated that structure–persistence relationships vary significantly across guilds, and the network‐level effects of network architecture can be reversed, negligible, or biased in specific guilds. These findings advance our understanding of how network architecture influences ecosystem stability and underscore the importance of considering multiple interaction types when predicting community dynamics.

Impacts of forest restoration on multifaceted bird diversity and community assembly in the Loess Plateau of China - Dexi Zhang; Ruirui Mao; Mingxin Liu; Qian Zhou; Yizhu Wang; Xingfeng Si; Changming Zhao; Lixun Zhang (Forest Ecology and Management, 2024)

Effects of urbanization and vegetation on bird diversity in a megacity of central China - Liqing Peng; Qin Liu; Qiwei Wang; Xingfeng Si; Hongyu Niu; Hongmao Zhang (Biological Conservation, 2024)

Island biogeography of mixed‐species bird flocks: A gregarious nuclear species influences island area effects - Ari Martínez; Liping Zhou; Xingfeng Si; Ping Ding; Eben Goodale (Journal of Biogeography, 2024)
Aim Island biogeography theory has been extended to include various species interactions, but has yet to consider intraguild mutualisms. We compare species‐area relationships for mixed‐species flocks to those for the entire bird community and determine how ‘nuclear’ species, those important to flock formation or cohesion, which often have functional traits such as intraspecific gregariousness, influence flock species richness. We hypothesized that mixed flocks would only form on large islands where nuclear species are present. On the subset of larger islands, we expected flock species richness to rise with island area, reflecting a larger pool of species. Location Thirty‐one islands of varying area in the reservoir system of Thousand Island Lake, China. Taxon The resident forest bird community and its subcomponent of flock participants. Similar to elsewhere in southern China, the primary nuclear species was Huet's Fulvetta ( Alcippe hueti ), which averaged 20 individuals per flock, and led the flocks when present. Methods Birds were surveyed in the winter of 2017 and the autumn of 2021. Results The probability for a flock to be present, and the species richness of birds per transect, increased with island area, but the species richness of flocks did not. Flocks with Huet's Fulvetta were only found on islands larger than 30 ha. Flocks on smaller islands formed around secondary nuclear species typical of northern Chinese flocks. Main Conclusion Gregariousness as a functional trait may make nuclear species more susceptible to disappearing in small fragments, leading to flock collapse. The extreme gregariousness of fulvettas may also act to increase competition in the flocks they lead and limit the flocks' species richness. We encourage further comparisons of the species‐area curves of mixed‐species flocks and whole bird communities to better understand the influence of flocks on community assembly and species diversity.

Island biogeography of soundscapes: Island area shapes spatial patterns of avian acoustic diversity - Peng Han; Yuhao Zhao; Yi Kang; Ping Ding; Xingfeng Si (Journal of Biogeography, 2024)
Aim The equilibrium theory of island biogeography predicts the positive species–area relationship and the negative species–isolation relationship, resulting in higher species richness on large and close islands. Unlike species richness, soundscape diversity integrates sound from various sources (e.g. biophony, geophony and anthrophony). However, how soundscape diversity varies with island area and isolation still needs to be tested. Here, we explored the island biogeography of bird soundscapes and the determinants of island attributes in shaping bird diversity and soundscape diversity. Location Thousand Island Lake, Zhejiang, China. Taxon Birds. Methods We recorded avian soundscapes by audio recorders and censused bird diversity by line transects on 20 land‐bridge islands. We calculated four acoustic indices (acoustic complexity index, bioacoustic index, acoustic evenness index and acoustic entropy index) to assess acoustic richness, evenness and heterogeneity to explore the soundscape diversity of birds. We used multiple linear regressions, spatial autoregressions and piecewise structural equation models to examine the relationships between bird richness and acoustic diversity, and island attributes. Results We found positive diversity–area relationships for avian soundscapes. Larger islands had more vocal species and higher habitat diversity, which led to an increment in the richness and unevenness of avian soundscapes on large islands. Acoustic evenness decreased with increasing isolation (distance to the mainland). Main Conclusions Soundscapes on large islands are more diverse than those on small islands. Rich acoustic assemblages and heterogeneous habitats promote increased soundscape diversity on islands. Conversely, the lack of vocal contributors, resulting in a decrement in the communication of acoustic signals, can create a lower soundscape diversity on small and remote islands. Our study emphasizes the necessity of examining both species and habitat diversity in island biogeography for better understanding the underlying mechanisms determining biological soundscapes on islands.

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

Uncovering widespread Anthropocene dietary shifts in Chinese large mammalian herbivores - Yangheshan Yang; Yuhao Zhao; Thomas A. Stidham; Xiangxu Liu; Xichao Zhu; Bicheng Li; Lixun Zhang; Xijun Ni; Xingfeng Si (Ecology Letters, 2024)
The Anthropocene's human‐dominated habitat expansion endangers global biodiversity. However, large mammalian herbivores experienced few extinctions during the 20th century, hinting at potentially overlooked ecological responses of a group sensitive to global change. Using dental microwear as a proxy, we studied large herbivore dietary niches over a century across mainland China before (1880s–1910s) and after (1970s–1990s) the human population explosion. We uncovered widespread and significant shifts (interspecific microwear differences increased and intraspecific microwear dispersion expanded) within dietary niches linked to geographical areas with rapid industrialization and population growth in eastern China. By contrast, in western China, where human population growth was slower, we found no indications of shifts in herbivore dietary niches. Further regression analysis links the intensity of microwear changes to human land‐use expansion. These analyses highlight dietary adjustments of large herbivores as a likely key factor in their adaptation across a century of large‐scale human‐driven changes.

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Characterizing bird species for achieving the win-wins of conserving biodiversity and enhancing regulating ecosystem services in urban green spaces - Xiangxu Liu; Yuhao Zhao; Di Zeng; Yangheshan Yang; Wande Li; Yi Kang; Guangpeng Wei; Xiao Yuan; Shunqi Bo; Xingfeng Si (Urban Forestry & Urban Greening, 2023)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

SLOSS ‐based inferences in a fragmented landscape depend on fragment area and species–area slope - Jinliang Liu; Zachary G. MacDonald; Xingfeng Si; Lingbing Wu; Di Zeng; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2022)
Aims Whether a Single Large Or Several Small (SLOSS) habitat patches contain more species is central to the debate about how habitat fragmentation threatens species diversity. However, the geographical and biogeographical variables that affect emergent SLOSS patterns remain poorly understood. Here, we quantified SLOSS‐based diversity patterns of woody plant, bird and spider assemblages in a subtropical archipelago of land bridge islands. Location Thousand Island Lake, Zhejiang Province, China. Taxon Woody plants, birds and spiders. Methods We analysed species accumulation curves and species–area relationships (SARs) to quantify SLOSS‐based patterns of all, common and rare species for each taxon across different groupings of islands. Differences in the number of species between a single large island and sets of several small islands were measured in these analyses using a Saturation index (SI) and SLOSS index. Generalized additive models were used to assess the relationships between SI and SLOSS index values and the maximum area of islands included in the analysis, the slope of SARs (i.e. z ‐score) and the degree of nestedness. Results SI values increased with the maximum area of islands for three taxa, while SLOSS index values only increased with the maximum island area for woody plants. SI values increased as z ‐scores of woody plants decreased, and showed a quadratic relationship for birds and spiders. SLOSS index values decreased as z ‐scores of three taxa increased. The degree of nestedness and SI values or SLOSS index values were weakly correlated with all, rare and common species in the three taxa. Main conclusions SLOSS‐based inferences of fragmentation effects are contingent on variation in the maximum area of patches included in analyses and the slope of SARs in fragmentated landscapes. Whether conservation efforts should prioritize a single large or several small patches depends on the geographical (e.g. maximum fragment area) and biogeographical (e.g. slope of SAR) attributes of a fragmentated landscape.

A landscape‐level analysis of bird taxonomic, functional and phylogenetic β‐diversity in habitat island systems - Chi Zeng; Wande Li; Ping Ding; Yu Peng; Lingbing Wu; Xingfeng Si (Journal of Biogeography, 2022)
Aim How β‐diversity patterns are shaped by landscape‐level processes remains unclear across habitat island systems. Here we assessed landscape‐level bird β‐diversity in habitat island systems and aimed to (1) evaluate the relative contribution of turnover (β SIM ) and nestedness‐resultant (β SNE ) components to multisite β‐diversity (β SOR ) from taxonomic, functional and phylogenetic dimensions; (2) examine the influence of climate factors and system characteristics in shaping landscape‐level patterns of β‐diversity measures; and (3) study how β‐diversity patterns of bird communities vary with the spatial extents of island systems. Location Global. Taxon Birds. Methods We compiled bird data in 22 habitat island systems from literature and classified these island systems into small and large spatial scales. We partitioned β SOR into β SIM and β SNE from three dimensions for each system and calculated standardized functional and phylogenetic β‐diversity measures. We assessed the effects of climate factors and system characteristics on observed and standardized β‐diversity measures by multiple linear models for both small and large systems. Results We found that the dominant role of β SIM to β SOR in habitat island systems was pervasive. However, the best explanatory variables were not consistent across systems, which depended on the β‐diversity components, diversity dimensions and spatial extent of habitat island systems. In general, climate factors acted as the main drivers of bird communities across small and large systems, whereas system characteristics played minor roles. Main conclusions Spatial turnover dominated overall bird β‐diversity in most habitat island systems. Our results imply the roles of niche‐based assembly processes through the interplay among differential functional traits and phylogenetic distances of species, climate factors and system characteristics as well as spatial extent in driving bird communities across multiple habitat island systems at a landscape level. This study offers a better understanding of the processes underlying macroecological patterns of isolated biological communities across habitat island systems.

Phylogenetic and functional clustering illustrate the roles of adaptive radiation and dispersal filtering in jointly shaping late‐Quaternary mammal assemblages on oceanic islands - Xingfeng Si; Marc W. Cadotte; T. Jonathan Davies; Alexandre Antonelli; Ping Ding; Jens‐Christian Svenning; Søren Faurby (Ecology Letters, 2022)
Islands frequently harbour unique assemblages of species, yet their ecological roles and differences are largely ignored in island biogeography studies. Here, we examine eco‐evolutionary processes structuring mammal assemblages on oceanic islands worldwide, including all extant and extinct late‐Quaternary mammal species. We find island mammal assemblages tend to be phylogenetically clustered (share more recent evolutionary histories), with clustering increasing with island area and isolation. We also observe that mammal assemblages often tend to be functionally clustered (share similar traits), but the strength of clustering is weak and generally independent from island area or isolation. These findings indicate the important roles of in situ speciation and dispersal filtering in shaping island mammal assemblages under pre‐anthropogenic conditions, notably through adaptive radiation of a few clades (e.g. bats, with generally high dispersal abilities). Our study demonstrates that considering the functional and phylogenetic axes of diversity can better reveal the eco‐evolutionary processes of island community assembly.

Host plant environmental filtering drives foliar fungal community assembly in symptomatic leaves - Xiang Liu; Pu Jia; Marc W. Cadotte; Chen Zhu; Xingfeng Si; Yunquan Wang; Fei Chen; Jihua Wu; Shurong Zhou (Oecologia, 2021)

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Island area, not isolation, drives taxonomic, phylogenetic and functional diversity of ants on land‐bridge islands - Yuhao Zhao; Robert R. Dunn; Haonan Zhou; Xingfeng Si; Ping Ding (Journal of Biogeography, 2020)
Aim To explore the impact of island area and isolation on multiple dimensions of ant biodiversity (taxonomic, phylogenetic and functional diversity) and the underlying processes of community assembly on islands. Location Thousand Island Lake, Zhejiang, China, created by dam construction in 1959. Taxon Ants. Methods We sampled ants on 33 islands, built a species‐level phylogenetic tree and measured five morphological traits of all species collected to estimate taxonomic, phylogenetic and functional diversity. We used multiple linear regression models and null models to examine the relationships between diversity metrics and island variables (area and isolation). Results We recorded 97 ant species on the study islands. We verified positive diversity–area relationships for species richness, phylogenetic diversity and functional diversity. However, although functional and phylogenetic community structure were indistinguishable from random communities, phylogenetic structure tended to be clustered, whereas functional structure tended to be overdispersed. Additionally, we found the structure of ant communities shifted from phylogenetic and functional clustering on smaller islands to phylogenetic and functional overdispersion on larger islands. Main conclusions Our results support the hypothesis that environmental filtering is the dominant process structuring ant communities on smaller islands, and that competitive exclusion becomes more important on larger islands. Thus, island area acts as an important filter even though ant community structure on the study islands was indistinguishable from random communities. Moreover, our results show that environmental filtering influences phylogenetic community structure of ants, whereas competitive exclusion influences functional community structure of ants. These findings highlight the need to examine both phylogenetic and functional diversity in order to understand the mechanisms that govern the assembly of natural communities on islands.

Species richness, phylogenetic and functional structure of bird communities in Chinese university campuses are associated with divergent variables - Wenjing Zhang; Chenxia Liang; Jun Liu; Xingfeng Si; Gang Feng (Urban Ecosystems, 2018)

Seasonal variation in avian diversity and tolerance by migratory forest specialists of the patch-isolation gradient across a fragmented forest system - David A. Ehlers Smith; Xingfeng Si; Yvette C. Ehlers Smith; Colleen T. Downs (Biodiversity and Conservation, 2018)

Patterns of avian diversity across a decreasing patch‐size gradient in a critically endangered subtropical forest system - David A. Ehlers Smith; Xingfeng Si; Yvette C. Ehlers Smith; Riddhika Kalle; Tharmalingam Ramesh; Colleen T. Downs (Journal of Biogeography, 2018)
Aim We investigated habitat heterogeneity and patterns of avian taxonomic and functional diversity change across a decreasing patch‐size gradient in a critically endangered, fragmented forest‐system to elucidate: (1) habitat patch‐size and structural drivers of avian diversity change, (2) potential patch‐size thresholds at which avian diversity and habitat heterogeneity changes occurred and (3) avian species/communities within thresholds that indicated distinct patch‐size categories. Location Indian Ocean Coastal Belt, South Africa. Methods We conduced habitat‐structure and fixed‐radius point‐count surveys during the avian breeding season across 123 habitat patches (range 0.06–386.9 ha). We calculated taxonomic and functional diversity/patch (α) using a distance matrix of all traits present in the avian community (γ) and described community change across the patch‐size gradient (β). We compared linear regressions of patch‐size effects on avian functional α‐diversity and habitat‐structural heterogeneity to segmented regression at five bands, determined by mean patch sizes responsible for provisioning avian functional α‐diversity at Results Avian taxonomic and functional α‐diversity significantly decreased with decreasing patch size and habitat heterogeneity; correlations between taxonomic and functional diversity declines and a positive significant influence of habitat heterogeneity on avian functional diversity indicated selective extinction pressure on niches and concomitant functional traits. Species turnover significantly increased in smaller patches. Segmented regressions of patch size‐effect on avian functional diversity and habitat heterogeneity out‐performed linear regressions at three patch‐size thresholds (157, 96 and 9 ha). Forest‐dependent specialists were significant indicators of high‐diversity patches >90 ha. Species characterizing small patches Main conclusions Specialized niches and concomitant species became locally extinct at patch‐size thresholds. We present replicable methodology and recommendations for conservation of forest systems using a critically endangered biome containing disproportionately high avifauna.

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

When the species–time–area relationship meets island biogeography: Diversity patterns of avian communities over time and space in a subtropical archipelago - Xiao Song; Robert D. Holt; Xingfeng Si; Mary C. Christman; Ping Ding (Journal of Biogeography, 2018)
Aim The species–area ( SAR ) and species–time relationships ( STR ) are of vital importance in community ecology. Previous studies suggest that a unified, general species–time–area relationship ( STAR ) may hold, with non‐independent scaling of richness across space and time. Most STAR studies to date have considered species accumulation curves in relatively homogeneous habitats. Here, we test the generality of the STAR in an island system and assess how factors other than area influence species richness, accumulation and turnover through time. Location Thousand Island Lake, China. Methods We surveyed bird communities on 36 islands using line transects, and calculated annual species richness of breeding birds from 2007 to 2015. We built island STAR models at island (island STAR ; ISTAR ) and transect levels (local community–time–area relationship; LCTAR ). We employed partial correlations and multiple regressions to examine potential influences of island attributes other than area (i.e. isolation, edge effect and habitat richness) on slopes of STR s. Results ISTAR and LCTAR models explained 88.8% and 83.1% of total variance, respectively, and both models have a negative space–time interaction. Richness scales comparably in space and time, for both whole‐island and transect‐level analyses. The partial correlation analysis showed that distance to mainland and perimeter‐to‐area ratio are significantly positively correlated with the time scalar ( w ), and habitat richness and w are negatively correlated. Multiple regression models identify perimeter‐to‐area ratio as particularly influential. Main conclusions The STAR pattern generalized to an island system where species turnover is high, indicating an interdependency of time and space in determining species richness. Islands have attributes other than area that influence patterns of species accumulation and turnover through time. Ecologists should consider the interdependence of space and time when characterizing species richness patterns.

Do seasonal species assemblages differ in their biogeography? Evidence from the spatial structure of bird communities on land‐bridge islands - Chuanwu Chen; Marcel Holyoak; Xingfeng Si; Yanping Wang; Ping Ding (Journal of Biogeography, 2018)
Aim We tested the effects of season and migratory status (residents‐versus‐seasonal migrants) on island biogeography of bird assemblages through partitioning beta diversity into richness and turnover components and community nestedness metrics. We predicted that total beta diversity, the richness component of beta diversity and community nestedness will be lower for bird assemblages in winter than in summer, and lowest of all for winter visitors. These predictions were derived from published ideas about resource availability, movement and habitat choice in birds in different seasons. Location Thousand Island Lake, China. Methods Bird species were sampled using line transects on 36 islands during five breeding and winter seasons (2009−2014). Birds were grouped into assemblages of winter residents, winter visitors and summer residents. Associations between beta diversity partitioning, island area, isolation and habitat richness were tested using partial Mantel correlations. We complemented these tests with measures of nestedness and null model approaches. Results Contrary to expectation, beta diversity, nestedness and difference of beta diversity or its components from null models were higher for winter residents than either summer resident or winter visitor assemblages. As predicted, winter visitors showed little association with habitat richness, and beta diversity was rarely different from null communities. Summer residents had the highest correlations of beta diversity components with habitat richness, but showed the lowest level of total beta diversity, a low richness component and were anti‐nested (less nested than random). Main conclusions Substantial differences were found in the biogeography of winter‐versus‐summer residents, and seasonal visitor (migratory)‐versus‐resident bird assemblages, which match expectations derived from bird biology and population ecology. Summer residents highlighted the role of habitat‐related niche differences, whereas winter residents showed area‐related selective extinction. By contrast, winter visitors appeared to be more randomly distributed.

Dispersal modality determines the relative partitioning of beta diversity in spider assemblages on subtropical land‐bridge islands - Lingbing Wu; Xingfeng Si; Raphael K. Didham; Dapeng Ge; Ping Ding (Journal of Biogeography, 2017)
Aim To identify geographical drivers determining the relative partitioning of species replacement and richness difference or nestedness‐resultant components of beta diversity in spider groups with differing dispersal modalities. Location Thousand Island Lake, China. Methods We sampled spider assemblages on 31 land‐bridge islands for two years. Each species was classified into a dispersal group based on ballooning propensity (frequent, occasional or non‐ballooners). Two frameworks were used to separate beta diversity (β cc or β jac ) of each group into either species replacement (β ‐3 ) and richness difference (β rich ) components, or turnover (β jtu ) and nestedness‐resultant (β jne ) components. Mantel and partial Mantel tests were performed to determine correlations between pairwise dissimilarities and difference in island area, difference in distance to mainland and inter‐island distance for each group. Results The multiple‐island dissimilarity of spiders was primarily driven by turnover. Beta diversity (β cc or β jac ) was positively associated with difference in island area in frequent ballooners, and negatively associated with difference in island area in occasional ballooners. Difference in island area had positive effects on β jne for all groups, but negative effects on β ‐3 and β jtu for occasional or non‐ballooners. β rich was positively associated with difference in island area in frequent and non‐ballooners. We did not find any significant isolation effects for these three measures of dissimilarity. Main conclusions The dominant process of extinction resulted in a high contribution of turnover to the multiple‐island dissimilarity of spiders. Specifically, frequent ballooners contributed less turnover to multiple‐island dissimilarity than occasional and non‐ballooners. The most likely explanation for this is that frequent ballooners were potentially able to colonize all islands, whereas occasional and non‐ballooners were constrained by water barriers and were unable to occupy most islands. Contrasting dissimilarities among dispersal groups of spiders demonstrates the importance of beta diversity partitioning, and the mechanistic insight gained on trait‐dependence in community assembly.

Turnover of breeding bird communities on islands in an inundated lake - Xingfeng Si; Stuart L. Pimm; Gareth J. Russell; Ping Ding (Journal of Biogeography, 2014)
Aim MacArthur and Wilson's theory of island biogeography proposes that the rate at which species colonize an island depends on the island's isolation (distance effect), whereas the local extinction rate depends on its area (area effect). Alternative hypotheses recognize that area can affect the colonization rate (target effect) and that isolation can affect the extinction rate (rescue effect) and, moreover, that these relationships may dominate. We quantify these relationships and associated turnover rates and incidence using long‐term counts of breeding bird communities on islands in an inundated lake. Location Thousand Island Lake, China. Methods We assessed the occupancy and behaviour of breeding birds on 37 islands from 2007 to 2012. We estimated the effects of area, isolation and other biogeographical parameters on the frequencies of colonization and extinction events using multivariate logistic regression. We then extended these results to derived properties such as species turnover rates and incidence. Results Extinction rates decreased and colonization rates increased on larger islands. Isolation had no significant effect on colonization or extinction rates. Islands had high species turnover overall, and turnover rates followed the same pattern as extinction rates with different areas and isolations. Pool turnover, which controls for the number of species in the pool, was higher on large islands. Species richness also increased with area. Our study of bird communities supported area and target effects, but not distance and rescue effects. Main conclusions Island area was a better predictor of colonization and extinction than isolation, probably because of the relatively small scale ( c . 580 km 2 ) and homogeneous vegetation structure of our research system, and the strong dispersal ability of birds. We conclude that the differences between our observations and theoretical predictions, or results from other studies that measured colonization and extinction directly, are consistent with the particular biogeography of these islands.